АПЕНДИКУЛЯРНА МУЦИНОЗНА ЦИСТАДЕНОМА І ЦИСТОАДЕНОСАРКОМА В ГІНЕКОЛОГІЧНІЙ ПРАКТИЦІ. КЛІНІЧНІ ВИПАДКИ ТА ОГЛЯД ЛІТЕРАТУРИ - SKLYAROVА, V.О.; MAKSYMYUK, V.V.; CHAJKIVSKYJ, R.A.; PRYKUPENKO, O.V.; NEPYIVODA, O.M.; ROZHANSKYI, T.YU.; MARTYN, YU.T.; CHAJKIVSKA, V.R. (PH Akademperiodyka, 2025)
Tumors of the right uterine appendages cannot always be distinguished from mucous neoplasms of the appendix (MA) at the preoperative stage. According to the literature, MA is traditionally considered more common in women than in men at the age of 50 years, with a ratio of 4:1. We have identified 2 cases of surgical treatment of MA in gynecological practice, one of mucinous cystadenoma and the other of mucinous cystadenocarcinoma. We present the visual intraoperative assessment of the appendix condition in cystadenoma and cystadenocarcinoma, clinical manifestations, diagnostic discrepancies, and operative tactics. The literature on the detection of appendicular mucocele that mimics ovarian tumor formations in women has been reviewed. The features of diagnostics and possible diagnostic errors were summarized. Diagnostic laparoscopy, visual and operative clinical experience of the surgeon, and cytological and histological examinations of intra- and postoperative results allow for an adequate treatment. It is advisable that the stages and course of appendectomy be reviewed by operating gynecologists and, if necessary, general surgeons.